Review of Evolutionary Political Economy - Elsner, Wolfram; Lazaric, Nathalie; Nesvetailova, Anastasia; Stockhammer, Engelbert; Cincotti, Silvano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
EAEPE$1 (Bs new international journal The Review of Evolutionary Political Economy (REPE) advances academic excellence in evolutionary political economy. We invite high-quality conceptual and review articles and cutting-edge methodological and empirical studies from evolutionary and international political economy, and heterodox, computational and complexity economics. Papers should embrace the heterogeneity of economic agents and interactions as complexified by power, institutions and environmental inputs. Papers might explore the origins and impact of economic crises, inequality and unemployment, the changing role of finance and financial instability, the digital transformation, and the socio-economic facets of environmental degradation and climate change. Articles that advance interdisciplinary analyses of complex systems, embrace social, natural, behavioural and computer sciences or draw on humanities and cultural theories are welcome. We also accept review articles for groups of books on certain areas. These should cover at least three books and should not exceed 4,000 words. REPE$1 (Bs special issues may cut across conventional themes and disciplines and relate evolutionary political economy to real-world issues. Ideas and proposals from guest-editors are invited.s
Keywords: Economics; Institutional/Evolutionary Economics; International Political Economy; Political Economy/Economic Systems